Фізико-механічні властивості cbn композитів зі зв'язками на основі карбідів TI, CR, V в умовах високошвидкісного точіння AISI 316L - Сліпченко, Катерина Вячеславівна; Петруша, Ігор Андрійович; Туркевич, Володимир Зіновійович (НТУ "ХПІ", 2018)
Досліджено механічні властивості та експлуатаційні характеристики різального матеріалу на основі кубічного нітриду бору зі зв’язками у виді карбідів перехідних металів (Ti, Cr, V), алюміній був введений в шихту якості гетеру. Композити одержано шляхом термобаричного спікання в апараті високого тиску типу тороїд. Виявлено, що зразки спечені в температурному інтервалі 2000-2150 °С демонструють найвищу зносостійкість в умовах високошвидкісного точіння нержавіючої сталі AISI 316L.

In current paper, we report on mechanical properties and wear resistance of high pressure high temperature (HPHT) sintered cutting tool materials based on cBN with carbides of transition metals Ti, Cr, V used as binders. Itial mixtures of compositions were chosen with 60 vol. % of cBN, 35 vol. % of binder phase and 5 vol. % of Al. Aluminum was introduced into the starting mixture as an oxygen getter. Sintering were conducted in HPHT toroid type apparatus under pressure of approx. 7,7 GPa and in the temperature range of 1600-2450 °С. Elastic properties were measured using the ultrasonic pulse-echo technique. The highest tool wear resistance is demonstrated by the tools sintered at 2000-2150 °С during machining of AISI 316L. It was found that samples sintered in the temperature range of 2000-2150 °C demonstrate the highest wear resistance while machining of stainless steel AISI 316L.
Physico-mechanical properties of cbn composites with binders based on carbides of TI, CR, V in conditions of high-speed machining of AISI 316L
Keywords: титан; ванадій; хром; сталь; високий тиск; твердість; turning; high pressure; vanadium; chromium